PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GLOBAL BERKAH SENTOSA DI KARAWACI TANGERANG - Anis Fitriyah; Anisa Nurdina (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of leadership style and work discipline on employee performance at PT. Global Berkah Sentosa in Karawaci Tangerang, either partially or simultaneously. The research method used in this research is a quantitative method. The sample used was 92 respondents using the Slovin formula. The data analysis methods used in this research were instrument test, classical assumption test, simple linear and multiple linear regression tests, correlation coefficient test, determination test, t test and f test. The results of this research show that Leadership Style (X1) have positive and significant effect on employee performance (Y). This can be proven by the results of data processing from the calculated t value of 15.622 > t table 1.9869, and a significant probability level of 0.000 < 0.05. Work Discipline (X2) have positive and significant effect on employee performance (Y), this can be proven by the results of data processing from the calculated t value of 15.738 > t table 1.9869 and a significant probability level of 0.000 < 0.05. Leadership style and work discipline simultaneously have a significant effect on employee performance, this is proven by the results of data processing f calculated 167.587 > f table 3.10 and the significant probability level is 0.000 < 0.05. The correlation coefficient value is 0.889. Leadership style and work discipline have a positive and significant effect on employee performance with the multiple regression equation Y=0.448X1+0.490X2. Then an R square of 0.790 was obtained, indicating that the influence of leadership style and work discipline variables contributed 79% to employee performance, while the remaining 21% was influenced by other factors not explained in this research.